Analisis Perkembangan Bahasa Ekspresif Anak dengan Gangguan Bicara pada Usia 5 Tahun - Syarifa Dita Nadia; Sri Indriani Harianja; Asih Nur Ismiatun (Institut Nalanda, 2026)
This study aims to analyze and describe the expressive language development of 5-year-old children at TK Kemala Bhayangkari 29 Jambi City and to identify the factors that influence the expressive language development of 5-year-old children at TK Kemala Bhayangkari 29 Jambi City. This research used a qualitative method with a descriptive approach. The study was conducted at TK Kemala Bhayangkari 29 Jambi City during the even semester of the 2025/2026 academic year. The informants in this study were selected using purposive sampling, consisting of teachers and parents. Another informant was one student from TK Kemala Bhayangkari 29 who became the research subject. Data collection techniques were carried out through in-depth interviews, observations, and documentation. Data analysis techniques used the Miles and Huberman model, including data collection, data reduction, data presentation, and conclusion drawing/verification. This study used source, technique, and time triangulation to test the credibility of the collected data. The results showed that the expressive language ability of AYB, a 5-year-old child, had not developed optimally. AYB was able to understand simple conversations, answer questions, and participate in short conversations; however, the child still experienced difficulties in expressing ideas, feelings, and experiences in a structured manner. The child tended to use short sentences, some word pronunciations were unclear, and still needed stimulation to initiate communication, especially in the school environment. Therefore, AYB requires continuous stimulation and guidance to improve sentence construction skills, enrich vocabulary, improve pronunciation, and build confidence in communicating.